Framework for Dataset Development in Building Energy Balance Simulations - Alyokhina, Svitlana; Orlova, Natalia (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The article presents a structured approach to forming initial datasets necessary for calculating the energy balance of buildings, tailored to the district's level of digitalization. The methodology outlined addresses the often-neglected step of data preparation, which critically influences the outcomes of energy balance simulations. Two distinct process flows for dataset formation are introduced, reflecting high and medium levels of district digitalization. The paper’s novelty lies in formalizing the dataset creation process, enabling more accurate energy simulations, particularly in the early planning stages of positive energy districts.